2018
DOI: 10.5195/ijms.2018.24
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors and Diabetes in Medical Students: Observational Study, Experience in Colombia

Abstract: Background: Cardiovascular Disease is a leading cause of preventable death. Cardiovascular risk factors’ identification is the cornerstone for effective and early interventions decreasing the frequency of acute health-threatening events. Since adolescence and youth are very vulnerable stages to develop risky habits, we decided to run this study in the Multidisciplinary Universitary Camp for Research and Service. Methods: A descriptive cross-sectional study was performed in the Multidisciplinary Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Obesity, NAFLD and T2DM also share a common feature with cognitive impairment and neurodegenerative disorders, i.e. target organ-insulin resistance, in which the contribution of oxidative stress is well established [34][35][36][37]. Moreover, the involvement of oxidative stress in the development and progression of solid and haematological cancers has also been extensively studied and explained by various pathogenic mechanisms, including low-grade chronic inflammation, also found in obese patients [38][39].…”
Section: Resultsmentioning
confidence: 99%
“…Obesity, NAFLD and T2DM also share a common feature with cognitive impairment and neurodegenerative disorders, i.e. target organ-insulin resistance, in which the contribution of oxidative stress is well established [34][35][36][37]. Moreover, the involvement of oxidative stress in the development and progression of solid and haematological cancers has also been extensively studied and explained by various pathogenic mechanisms, including low-grade chronic inflammation, also found in obese patients [38][39].…”
Section: Resultsmentioning
confidence: 99%
“…10 Another 2016 study measured the prevalence of hypertension and cardiovascular disease risk factors among 180 medical students, out of which 7.8% were overweight and 2% were obese. 28 A study analysing the lipid profile of 153 medical students showed that 15% were overweight and 2.6% were obese. 29 A study investigating the prevalence of cardiovascular disease risk factors among 433 medical students from east India showed that 70% of the sample were obese.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with T2DM and CVD who have LDLc >70 mg/dL and are already receiving the maximum tolerated statin dose may benefit by taking another lipid-lowering drug, but with another mechanism of action (e.g., ezetimibe) [25]. Irrespective of the currently available armamentarium in the management of T2DM and related conditions, lifestyle adjustments and the primary prevention of T2DM, CHD or dyslipidemia remain of uttermost importance [26]. Lifestyle interventions remain, however, difficult to implement, even in subjects who are aware of the risks of an unhealthy diet and of sedentarism, such as medical students and physicians [27][28][29].…”
Section: Discussionmentioning
confidence: 99%